Diopside-based glass-ceramics from MSW fly ash and bottom ash - Qian, Guangren (Waste management (New York, N.Y.), 2006)
By utilising MSW fly ash from the Shanghai Yuqiao municipal solid waste (MSW) incineration plant as the main raw material, diopside-based glass-ceramics were successfully synthesized in the laboratory by combining SiO(2), MgO and Al(2)O(3) or bottom ash as conditioner of the chemical compositions and TiO(2) as the nucleation agent. The optimum procedure for the glass-ceramics is as follows: melting at 1500 degrees C for 30 min, nucleating at 730 degrees C for 90 min, and crystallization at 880 degrees C for 10h. It has been shown that the diopside-based glass-ceramics made from MSW fly ash have a strong fixing capacity for heavy metals such as lead (Pb), chromium (Cr), cadmium (Cd) etc